Predictive Value of HFA-PEFF Score in Patients With Heart Failure With Preserved Ejection Fraction - Sun, Yuxi; Si, Jinping; Li, Jiaxin; Dai, Mengyuan; King, Emma; Zhang, Xinxin; Zhang, Yanli; Xia, Yunlong; Tse, Gary; Liu, Ying (Frontiers in Cardiovascular Medicine, 2021)
Aims: HFA-PEFF score has been proposed for diagnosing heart failure with preserved ejection fraction (HFpEF). Currently, there are only a limited number of tools for predicting prognosis. In this study we evaluated whether the HFA-PEFF score can predict mortality in HFpEF patients. Methods: This single-center, retrospective observational study enrolled patients diagnosed with HFpEF at the First Affiliated Hospital of Dalian Medical University between 1st January 2015 and 30th April 2018. The subjects were divided according to their HFA-PEFF score into low (0-2 points), intermediate (3-4 points), and high (5-6 points) score groups. The primary outcome was all-cause mortality. Results: A total of 358 patients (mean age: 70.21 ± 8.64 years, 58.1% female) were included. Of these, 63 (17.6%), 156 (43.6%), and 139 (38.8%) were classified into the low, intermediate, and high score groups, respectively. Over a mean follow-up of 26.9 months, 46 patients (12.8%) died. The percentage of patients who died in the low, intermediate, and high score groups were 1 (1.6%), 18 (11.5%) and 27 (19.4%), respectively. Multivariate Cox regression identified HFA-PEFF score as an independent predictor of all-cause mortality (HR:1.314, 95% CI: 1.013-1.705, P=0.039). Cox analysis demonstrated a significantly higher rate of mortality in the intermediate (HR: 4.912, 95% CI 1.154-20.907, P = 0.031) and high score groups (HR: 5.291, 95% CI: 1.239-22.593, P=0.024) than the low score group. Receiver operating characteristic (ROC) analysis indicated that the HFA-PEFF score can effectively predict all-cause mortality after adjusting for age and NYHA class (AUC 0.726, 95% CI 0.651-0.800, P=0.000). With a HFA-PEFF score cut-off value of 3.5, the sensitivity and specificity were 78.3% and 54.8%, respectively. The area under the curve (AUC) on ROC analysis for the biomarker component of the score was similar to that of the total score. Conclusions: The HFA-PEFF score can be used both to diagnose HFpEF and predict prognosis. Higher scores are associated with a higher all-cause mortality. Key Words: HFpEF, HFA-PEFF score, all-cause mortality, predictive value, prognosis